Touristic routes in the buffer zone of the Alberto Manuel Brenes Biological Reserve (ReBAMB) - Moya Calderón, Michael Mauricio (2017)
The Alberto Manuel Brenes Biological Reserve (ReBAMB) covers 7,800 hectares and represents the main forest block in San Ramón (Alajuela, Costa Rica). Due its Biological Reserve status (a management category), the activities that can be carried out at the reserve are very limited and restricted to two main goals: conservation and research. The buffer zone of approximately 28,552 hectares, surrounding the ReBAMB, is also very important in terms of conservation and development. Among other goals, the buffer zone promotes sustainable activities, such as Ecotourism. The Ecotourism projects have been emerging in some towns located within the buffer zone, an area where the natural richness is definitely the main attraction for visitors.Most of the targeted initiatives were low budget projects belonging to local families. We conducted a study to identify the main historical, cultural and natural attractions as well as the available touristic services. We proposed four different touristic routes in the buffer zone, with the purpose of creating an attractive touristic product that promotes sustainable development in this zone. The routes are: Ruta Bosque Nuboso La Paz, Ruta Ecológica de Aventura San Ramón, Ruta del Quetzal Agroecoturística Zapotal, Ruta de Observación de Aves.